Residual effects of nematode control in rice fields infested with Hirschmanniella mucronata and H. oryzae - Soriano, I. R. S. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 1995)
Residual effects of carbofuran treatments and cropping of Sesbania rostrata on rice root nematode population and rice yield were studied in two paddy fields infested with Hirschmanniella mucronata or H. oryzae. In both fields, a crop of S. rostrata reduced the nematode population for two successive rice crops and increased yields. In the H. rostrata in both oryzae infested field, a carbofuran treatment reduced the nematode population for two successive rice crops and increased the yield of three rice crops. The yield of the second rice crop grown after a cropping of. fields and the yield of the third rice crop grown after a carbofuran treatment were correlated with the nematode population observed after the previous rice crop. The increase in rice yield, therefore, could be attributed not only to the fertilizer effect brought about by growing of S. rostrata or green manure application but also to the control of the rice root nematode.